Anomalously large magnetostriction caused by rearrangement of magnetoelastic domains - Kalita, V.M.; Lozenko, A.F.; Ryabchenko, S.M.; Trotsenko, P.A.; Yatkevich, T.M. (Functional Materials, 2004)
Anomalous large values of magnetostriction related to rearrangement of multidomain state in easy-plane antiferromagnetics of iron group dihalides have been shown to be associated with magnetoelastic nature of the multidomain state. To describe that multidomain state, a parameter has been introduced which characterizes the average orientation of domains. The parameter is referred to as the domain co-alignment one.